Las entidades financieras de economía social ante la crisis financiera: un análisis de las cajas rurales españolas - Palomo Zurdo, Ricardo; Sanchís Palacio, Joan Ramón; Soler Tormo, Francisco (REVESCO. Revista de Estudios Cooperativos, 2010)
The small farm loan banks, as their credit organizations, like the banks and the savings banks, are undergoing the derived consequences of the present international financial crisis. Nevertheless, far from supposing a ballast for these organizations, the present situation has to be taken advantage of like an opportunity, which means to redefine its model of business betting by a greater efficiency. The objective of the present work is to analyze which are the effects that the financial crisis is causing in the Spanish small farm loan banks, starting off of the own characteristics of the small farm loan banks and considering the published most recent works on the present financial crisis. The surroundings of global financial crisis require a comparative characterization of the sector with the bank and the savings banks by means of the analysis of the rates of dilatoriness, cover of insolvencies and the granted ratings.
Keywords: Small farm loan banks; Financial Crisis; Efficiency; Dilatoriness; Credits; Rating